Forensic analysis of soman exposure using characteristic fragment ions from protein adducts. (September 2021) - Fu, F; Guo, Y; Lu, X; Zhao, P; Zou, S; Wang, H; Gao, R; Pei, C
The verification of exposure to nerve agents is a serious challenge, especially in cases of soman (GD) poisoning. Protein adducts are reliable biomarkers, that provide forensic information and evidence during incidents of terrorism or sporadic poisoning. Mass spectrometry, coupled with a proteomics approach, was established for the forensic analysis of GD-based protein adducts. The fragmentation pathways of GD-based protein adducts were investigated for the first time using electrospray ionization tandem mass spectrometry. Three abundant natural loss product ions, [M+2H-54] 2+ (loss of two carbon cations), [M+2H-72] 2+ (loss of tert -butyl and methyl moieties), and [M+2H-84] 2+ (loss of the pinacolyl moieties), were observed in each of the GD-labeled adducts, and the product ions were independent of protein structure and exposure route. A unique mechanism for the formation of product ions involving GD-protein adducts is proposed here. These findings support the development of a simple and precise forensic analysis technique to rapidly verify GD poisoning using these three GD-related product ions.